Uji Daya Hambat Ekstrak Etanol Daun Tapak Kuda Ipomoea pes-caprae Terhadap Pertumbuhan Bakteri Propionibacterium acne - Etrin Z. E. Saputra Linggar; Eka Astuty; Yuniasih M.J. Taihuttu (Jurnal Ilmu Alam dan Lingkungan, 2021)
Ipomoea pes-caprae is a plant that has the ability as an anti-bacterial. The active compounds of Tapak Kuda leaves as anti-bacteria are flavonoids, alkaloids, and tannins. The purpose of this study was to determine the ability of the ethanol extract of tapak kuda leaves to inhibit the growth of Propionibacterium acne bacteria. This research is a laboratory experimental study using the disc diffusion method and using various extract concentrations of 5%, 10%, 25%, 50%, and 100%. The ethanol extract of tapak Kuda leaves was obtained from the maceration process of tapak Kuda leaves with ethanol solvent, then tested the inhibition of Propionibacterium acne. The parameters observed were the clear zone formed on the growth of Propionibacterium acne bacteria. The results showed that the ethanol extract of tapak Kuda leaves had a low ability to inhibit the growth of Propionibacterium acne bacteria. The clear zone formed at a concentration of 100% was only 1.14 mm while at a concentration of 5%, 10%, 25% and 50% there was no clear zone formed.